Empathy in Helping Professions: A Scoping Literature Review - Diswantika, Noviana; Rusmana, Nandang; Suherman, Uman; Qurbi, Abdullah (KONSELOR, 2025)
Weak empathy results in a lack of destructive behaviour in social life, intolerance, and discrimination. Empathy is a more comprehensive and profound concept than conventional empathy. This study is a scoping literature review that aims to identify what is known about empathy in helping professions. A systematic search was conducted on electronic databases, namely ScienceDirect, PubMed, Scopus, Journal Nasional, and Taylor and Francis, studies from 2010-2025. Data analysis used PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The results of the study were mapped based on the following criteria: conceptualisation of empathy, factors in the development of empathy, and research on the development of empathy, and data analysed based on content analysis. The research findings show that applicable to various fields of helping professions. Factors that can influence empathy are divided into constructive empathy development, including altruism, cooperation, compassion, morality, justice, and happiness. However, destructive empathy development is related to ability, feelings, people, individuals, capacity, pain, social behaviour, and deficits. Research on empathy has developed significantly, especially in the fields of health and psychology, using quantitative research. However, further analysis is needed to develop a conceptual analysis of empathy that focuses on other fields of expertise in a more specific and comprehensive manner, taking into account the aspects, factors, and validity of empathy.